Bodiless - Roden, David (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): David Roden Title (English): Bodiless Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 116-117 Page Count: 2 Citation (English): David Roden, “Bodiless,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 116-117.